2009
DOI: 10.1152/ajpregu.00171.2009
|View full text |Cite
|
Sign up to set email alerts
|

The molecular effects of skeletal muscle myosin regulatory light chain phosphorylation

Abstract: (RLC) in skeletal muscle has been proposed to act as a molecular memory of recent activation by increasing the rate of force development, ATPase activity, and isometric force at submaximal activation in fibers. It has been proposed that these effects stem from phosphorylation-induced movement of myosin heads away from the thick filament backbone. In this study, we examined the molecular effects of skeletal muscle myosin RLC phosphorylation using in vitro motility assays. We showed that, independently of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 86 publications
15
66
0
Order By: Relevance
“…In this scheme, straining the myosin traps ADP from ATP hydrolysis in the myosin active site by increasing the affinity of myosin for ADP so that the ADP from ATP hydrolysis becomes unexchangeable with the medium, making the myosin less sensitive to exogenously added ADP. This is consistent with observations of skeletal muscle myosin under strain (24,27), which also shows a strain-induced reduction in the affinity for exogenously added ADP. This is also consistent with a kinetic scheme in which there is a strain-dependent isomerization in the ADP-bound state (28).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this scheme, straining the myosin traps ADP from ATP hydrolysis in the myosin active site by increasing the affinity of myosin for ADP so that the ADP from ATP hydrolysis becomes unexchangeable with the medium, making the myosin less sensitive to exogenously added ADP. This is consistent with observations of skeletal muscle myosin under strain (24,27), which also shows a strain-induced reduction in the affinity for exogenously added ADP. This is also consistent with a kinetic scheme in which there is a strain-dependent isomerization in the ADP-bound state (28).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the reductions in force seen in these mutants could be due to changes in any of these parameters. It is unlikely that the mutations change the number of heads bound to the surface because neither phosphorylation of the RLC nor depletion of the RLC, both more drastic changes in the myosin structure than these one-amino-acid changes, alters the number of heads on the surface (6,23,24). Furthermore, the unloaded velocity and the unloaded duty cycle are statistically indistinguishable, suggesting that the step size of the myosin is unchanged by these mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is in the middle of the wide range reported by previous studies on heart muscle preparations that used noncardiac isoforms of MLCK (25,(31)(32)(33) and similar to the value (30-40%) reported for β-cardiac myosin in vitro (45). Enhancement of maximum isometric force by cRLC phosphorylation is also observed for skeletal muscle myosin (25), and the effects of RLC phosphorylation on the motor function of a range of muscle myosin isoforms have been attributed to an increase in the myosin lever arm stiffness (46,47) or step size (48).…”
Section: Length-dependent Activation and Crlc Phosphorylation May Usesupporting
confidence: 83%
“…Perry suggested that myosin light chains could exist as charged variants (Perrie et al 1972(Perrie et al , 1973, shortly after which phosphorylation was established as a significant mechanism in cardiac and skeletal muscle (Frearson and Perry 1975). Myosin RLC phosphorylationinduced enhancement of isometric force and increased rates of muscle contraction have been reported in a wealth of studies from different laboratories (Colson et al 2010;Davis et al 2001;Greenberg et al 2009;Scruggs and Solaro 2011;Sheikh et al 2012;Sweeney et al 1993;Warren et al 2012). Specifically, RLC phosphorylation was shown to accelerate the rate of cross-bridge entry into the force generating state by regulating the proximity as well as the interaction of myosin with actin, thereby increasing Ca 2+ sensitivity and amplitude of force at all activation levels (Colson et al 2010;Szczesna et al 2002).…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 99%